2020
DOI: 10.1590/0366-69132020663792926
|View full text |Cite
|
Sign up to set email alerts
|

Wollastonite/TCP composites for bone regeneration: systematic review and meta-analysis

Abstract: Composite biomaterials have gained notoriety in recent decades due to the ability to combine desirable properties of each material. Thus, associating bioactivity of wollastonite (W) with biodegradability of tricalcium phosphate (TCP) becomes promising for bone repair. Therefore, this study investigated, through systematic review and meta-analysis, in vivo studies that evaluated histomorphometrically the bone repair after implantation of W/TCP composites. The searches were performed in the PubMed/MEDLINE, LILAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…During the new biomaterials synthesis, CS and CaP have been choice materials (Nair et al, 2009;Sole;Grima, 2018) given this combination has shown promising results as bone substitutes used individually (Lin et al, 2009;Wang et al, 2012;Santos et al, 2020).…”
Section: Wollastonite and Tricalcium Phosphate Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the new biomaterials synthesis, CS and CaP have been choice materials (Nair et al, 2009;Sole;Grima, 2018) given this combination has shown promising results as bone substitutes used individually (Lin et al, 2009;Wang et al, 2012;Santos et al, 2020).…”
Section: Wollastonite and Tricalcium Phosphate Compositesmentioning
confidence: 99%
“…Although p-W is stable polymorphic silica at temperatures above 1030ºC, it has a crystalline structure capable of directly connecting with bone tissue De Aza, 1994). For biomedical purposes, W has been synthesized, processed, and used in different geometric presentation formats and shapes, such as metal alloy coatings, microspheres, granules, or sintered or non-sintered porous 3D scaffolds (Sola;Grima, 2018;Yu et al, 2018;Ge et al, 2019;Srinath et al, 2019;Kamboj et al, 2020;Meireles;Santos et al, 2021;Monção et al, 2022). This is related to the fact that when compared to the other bone replacement materials used clinically, such as CaP, W has higher bioactivity due to the release effect of Ca 2+ and silicate (SiO3 2− ), substantial during the osteogenesis mechanism (Ni;Hesaraki et al, 2009;Yu et al, 2018;Ge et al., 2019).…”
Section: Wollastonite and Tricalcium Phosphate Compositesmentioning
confidence: 99%
“…Os biomateriais se tornaram essenciais para restaurar e regenerar no menor tempo possível estruturas e funções perdidas quando a reparação tecidual não pode ser concluída em razão da falta de suprimento sanguíneo. A perda extensiva de tecidos podem ser causadas por infeções, neoplasias, doenças congênitas e outros distúrbios do tecido ósseo (dos Santos et al, 2020).…”
Section: Introductionunclassified